Bioteknologi Kombucha Serai (Cymbopogon citratus) dengan Pemanis Stevia Berdasarkan Lama Fermentasi Terhadap Kuantitas Kandungan Vitamin C dan Kadar Antioksidan - Ilma Diana Fitri; Ambarwati Ambarwati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine the quantity of vitamin C content and antioxidant levels and determine the quality of the physical test of lemongrass kombucha using stevia sweetener based on fermentation time. The research methods used were quantitative and qualitative descriptive methods with experimental methods, Completely Randomized Design (CRD) using a factorial factor pattern (one factor), and three repetitions. The research results showed that lemongrass kombucha with fermentation times of 11 and 13 days both had a pH of 4. Meanwhile, the average vitamin C content of the 11-day fermentation was 21.56 (mg/100 g) from 3 repetitions and 24.66 (mg/100 g) for the 13-day fermentation. The average fermentation antioxidant content on day 11 was 84.10%, while on day 13 it was 84.70%. In conclusion, the vitamin C content and antioxidant levels increase as the fermentation process takes longer. So, the fermentation time has a significant effect on the vitamin C content and antioxidant levels, so lemongrass kombucha can be an alternative drink to replace tea drinks in general and is useful as a probiotic drink that is good for digestion. Keywords: Antioxidants, Kombucha, Stevia Sweetener, Lemongrass, Vitamin C